Report of the Special Committee on the Situation with regard to the Implementation of the Declaration on the Granting of Independence to Colonial Countries and Peoples for 2018 - United Nations Department for General Assembly; Conference Management (United Nations, 2018)
This is the official report annually submitted to the General Assembly by the Special Committee on the Situation with regard to the Implementation of the Declaration on the Granting of Independence to Colonial Countries and Peoples for 2018.